Weight Increase of Cotton Fibers During Swelling in Alkali as a Sensitive Measure of Cellulose Degradation in Ruminal Fluid - Simpson, Marion E. (1977)
Weight increase of cotton fiber in an 18% NaOH solution, termed “alkali-centrifuge” or “AC” value, was measured after incubation of either 1 g or 100 mg of the fiber in ruminal fluid. The AC response was a sensitive measure of cellulolytic activity. Thus, fiber incubated at 21 and 51°C exhibited major AC increases even when direct weight losses of the unswollen fiber were less than 2%. Similarly, progressive additions of acetic acid to ruminal fluid progressively depressed both AC response and direct weight loss, but the former was still easily measurable when the latter was not. In tightly closed, completely filled vials with high ratio of ruminal fluid to sample, AC increased greatly and rapidly, i.e., in 6 h. This time could be further reduced to 2 h by overnight “preincubation” of the ruminal fluid with cotton fiber before starting the test incubation. Certain surfactants used to aid wetting of the fiber had a low but measurable potency in inhibiting cellulose digestion, but other surfactants were non-inhibitory. The AC response was maintained when ruminal fluid was diluted with an equal amount of McDougall's “artificial saliva” solution.